γ' Fibrinogen as a Predictor of Survival in Amyotrophic Lateral Sclerosis - Pronto-Laborinho, Ana Catarina; Lopes, Catarina S.; Conceição, Vasco A.; Gromicho, Marta; Santos, Nuno C.; de Carvalho, Mamede; Carvalho, Filomena A. (Frontiers in Cardiovascular Medicine, 2021)
Amyotrophic lateral sclerosis (ALS) is an aggressive neurodegenerative disorder related to neuroinflammation that is associated with increased risk of thrombosis. We aimed to evaluate γ’ fibrinogen plasma level (an in vivo variant of fibrinogen) as a biomarker in ALS, and to test its role as a predictor of disease progression and survival. Sixty-seven consecutive patients with ALS were followed and the results were compared with the ones from 82 healthy blood donors. Patients were clinically evaluated at the time of blood sampling and on follow-up (every 3 months for the time of follow-up until death) by applying the revised ALS Functional Rating Scale. Human plasma γ’ fibrinogen concentration was quantified using a specific two-site sandwich kit enzyme-linked immunosorbent assay. We found, for the first time, a positive association between γ' fibrinogen concentration and survival in ALS patients: patients with higher γ’ fibrinogen plasma levels survived longer, and this finding was not influenced by confounders like age, gender, respiratory impairment, or functionality (ALSFRS-R score). Since increased levels have a positive impact on outcome, this novel biomarker should be further investigated in ALS.